A practical method for evaluating the in vivo efficacy of EVA-71 vaccine using a hSCARB2 knock-in mouse model. Issue 1 (1st January 2021) - Wu, Yong; Qu, Zhe; Xiong, Rui; Yang, Yanwei; Liu, Susu; Nie, Jianhui; Liang, Chunnan; Huang, Weijin; Wang, Youchun; Fan, Changfa
ABSTRACT: Hand-foot-and-mouth disease is a contagious disease common among children under 5 years old worldwide. It is caused by strains of enterovirus, especially EV-A71, which can lead to severe disease. Vaccines are the only way to fight this disease. Accordingly, it is necessary to establish an efficient and accurate methodology to evaluate vaccine efficacy in vivo . Here, we established a practical method using a hSCARB2 knock-in mouse model, which was susceptible to EV-A71 infection at 5–6 weeks of age, to directly determine the efficacy of vaccines. Unlike traditional approaches, one-week-old hSCARB2 mice were immunized twice with a licensed vaccine, with an interval of a week. The titre of antibodies was measured after 1 week. Mice at 4 weeks of age were challenged with EV-A71 intraperitoneally and intracranially, respectively. The unimmunized hSCARB2 mice displayed systemic clinical symptoms and succumbed to the disease at a rate of approximately 50%. High viral loads were detected in the lungs, brain, and muscles, accompanied by clear pathological changes. The expression of IL-1β, IL-13, IL-17, and TNF-α was significantly upregulated. By contrast, the immunized group was practically normal and indistinguishable from the control mice. These results indicate that the hSCARB2 knock-in mouse is susceptible to infection in adulthood, and the in vivo efficacy of EV-A71 vaccine could be directly evaluated in this mouse model. The method developed here may be used in the development of new vaccines against HFMD or quality control of licensed vaccines.